THE EFFECT OF PQ4R AND MIND MAPPING TO STUDENTS’ READING COMPREHENSION - Afif Ikhwanul Muslimin; Fitrana Harintama (Universitas Islam Negeri Mataram, Indonesia, 2019)
The study aims at proving the effectiveness of the PQ4R and Mind-Mapping strategies in helping students to achieve higher reading comprehension score. The study involved two groups of Electrical Engineering department of UMM which were drawn using random sampling technique. The experimental group was taught using PQ4R (Preview, Question, Read, Reflect, Recite, Review) and Mind-Mapping strategies meanwhile the control group was taught using Direct Reading Activity (DRA) strategy. it was proven that PQ4R and Mind-Mapping strategies were more effective in helping students achieve higher literal comprehension score in reading since the different marginal means of post-test between control and experimental groups was 33.67 and the students were trained to be more active learners.